Concentrate Substituted Cassava Top Fermented Cassava Pulp in Altered Levels on Growth Performance in Thai Native X Lowline Angus Crossbred Cattle - Sophany Morm; Savdy Net; Sokchea Vong; Thearak Yi; Sophary Khin; Sovannara Moun; Chantha Sat; Sophana Pech; Lymeng Roeun (Badan Penerbitan Fakultas Pertanian (BPFP), 2023)
The main objective is to investigate the effect of DCfCaP-substitute concentrate on growth performance and feed efficiency in Thai native x Lowline Angus crossbred cattle. The average initial body weight (IBW) was assigned 97±18.5 kg and 1-year age, 12 females of Thai native x Lowline Angus crossbred cattle. Dietary treatments were designed in a completely randomized design (CRD) to receive three feeding treatments, four replications per treatment with one cow per replicate. The feeding treatments were administered as follows: T1=100% concentrate + 0% DCfCaP (control), T2=67% concentrate + 33% DCfCaP, and T3= 33% concentrate + 67% DCfCaP on dry matter basis (DM). The results indeed showed that the initial body weight (IBW) and final body weight (FBW) were non-significantly different (P>0.05). The average daily gain (ADG) in T1 and T2 was 0.53 kg/day and 0.48 kg/day, and representative superscripts were in the same row, but there were differences in T3 was 0.05 kg/day (P<0.001). T1 used feed intake higher than T2 and T3 (P=0.003). So far, the feed conversion ratio (FCR) in groups T1 and T2 were non-different except T3 (P<0.001). In conclusion, DCfCaP could substitute concentrate up to 33% in the diet without being effective in Thai native x Lowline Angus crossbred cattle. Therefore, DCfCaP is recommended because it is an alternative source of animal feed and could contribute to controlling environmental contamination. So DCfCaP is recommended to supply to cattle.